PENGARUH MODEL PEMBELAJARAN GAME BASED LEARNING BERBANTUAN BAAMBOOZLE TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS MURID KELAS VIII SMP ISLAM AR-RAUDHOH - Amri Nasrullah; Hera Deswita; Arcat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Students' mathematical concept understanding ability in grade VIII of SMP Islam Ar-Raudhoh remains relatively low, as mathematics instruction has largely stayed conventional and fails to actively engage students, indicating the need for a more interactive model such as Game Based Learning assisted by Baamboozle. This study aims to determine whether this model affects students' mathematical concept understanding ability in grade VIII of SMP Islam Ar-Raudhoh. A quantitative, quasi-experimental approach with a Two-Group Posttest Only design was used. The population comprised 62 grade VIII students in the 2026/2027 academic year; the sample was drawn through simple random sampling, yielding class VIIIA as the experimental group and class VIIIB as the control group, 31 students each. Data were collected via a posttest tested for validity, difficulty level, discriminating power, and reliability, then analyzed using normality, homogeneity, and t-tests. Results showed the experimental class achieved an average posttest score of 76.08, higher than the control class's 55.65, with a t-value of 4.843 exceeding the t-table value of 2.0003 at 5% significance, so H0 was rejected. It is concluded that the model significantly affects students' mathematical concept understanding ability and can serve as an engaging, effective alternative mathematics teaching strategy.